Modeling and impedance analysis of a single DC bus-based multiple-source multiple-load electrical power system - Gao, Fei; Bozhko, Serhiy (Institute of Electrical and Electronics Engineers, 2016)
The impedance based stability assessment method has been widely used to assess the stability of interconnected systems in different application areas. This paper deals with the source/load impedance analysis of the droop-controlled multiple sources multiple loads system which is a promising candidate in the future more-electric aircraft (MEA). This paper develops a mathematical model of the PMSG-based variable frequency generation system, derives the output impedance of the source subsystem including converter dynamics and shows the effect of parameters variation on source impedance and load impedance. A dynamic droop controller is proposed to provide the active damping to the system. In addition, the impedance analysis is extended to a generalized single bus-based multiple sources multiple loads system in which power losses are also investigated. The aforementioned analytical result is confirmed by experimental results.